The Effect of Employee Trust on Customer Satisfaction With Positive Emotions As Moderating Variable - I Gede Wiyasa MS (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: To prove and analyze positive emotions as a moderating variable to influence customer trust Satisfaction at the “Simple Group” café in Surabaya and Gresik. Design/methodology/approach: The analysis carried out is quantitative analysis using multiple linear regression to answer the problem formulation and determine the effect of the variables that have been determined. Findings: The effect of the quality of employee trust on satisfaction moderated by positive emotions at the “Simple Group” coffee shop in Surabaya and Gresik. The results of the analysis can be concluded that customer satisfaction is largely determined by the company's trust given to employees who deal directly with customers. Where in this case satisfaction when interacting is that customers get comfortable and good service from employees of the